Deep Ocean Particle Flux in the Northern South China Sea: Variability on Intra-Seasonal to Seasonal Timescales - Tan, Shiru; Zhang, Jingjing; Li, Hongliang; Sun, Lin; Wu, Zezhou; Wiesner, Martin G.; Zheng, Hao; Chen, Jianfang (Frontiers in Earth Science, 2020)
Based on time-series sediment trap observation at 1003-m depth in the northern South China Sea from 2014 to 2015, we used sinking particle flux combined with remote sensing-derived environmental data to infer mechanisms of the biological carbon pump. Total particle flux, particulate organic carbon, CaCO3, and lithogenic (inorganic)fluxes peaked in winter and autumn but showed minima in summer, ranging from 59.7 to 413.2 mg m−2 d−1, 2.1 to 18.2 mg m−2 d−1, 32.9 to 197.9 mg m−2 d−1, and 12.0 to 73.6 mg m−2 d−1, respectively. Similarly, opal flux varied from 6.9 to 109.6 mg m−2 d−1, with a prominent peak in winter and minimum in summer. However, a secondary maximum of opal in autumn was barely noticeable compared with other components. A deeper mixed-layer depth related to the northeast monsoon and surface cooling, overlapping with the effect of cyclonic eddies, is responsible for the strong winter fluxes. When an anticyclonic eddy suppresses the subsurface nutrient supply, primary production and subsequent export flux in summer were reduced substantially. With respect to maximum lithogenic and CaCO3 fluxes in autumn, a large aerosol optical depth suggests the scavenging and mineral ballast effects as potential causes. This study highlights the importance of intra-seasonal physical processes (e.g., mesoscale eddies and aerosol deposition) to the deep particle flux in the South China Sea as well as monsoonal transition.